INVESTMENT OPPORTUNITY SET OF COMPANY VALUE WITH DIVIDEND POLICY AS MEDIATION ON MANUFACTURING COMPANIES - Azizatul Munawaroh; Sutanti Sutanti (Jurnal Ekonomi Trisakti, 2022)
This study aims to analyze whether IOS and dividend policy have a positive direct effect on firm value, and whether dividend policy mediates the indirect effect of IOS on firm value in manufacturing companies listed on the Indonesian stock exchange for the period 2017 to 2019. This study is a research study. quantitative analysis model with Pooled Least Square (PLS) with secondary data in the form of financial statements of manufacturing companies listed on the Indonesia Stock Exchange obtained through web.idx.co.id. Data analysis using Software Eviews Version 10. The population of this research is 182 companies listed on the Indonesian stock exchange. While the research sample is 33 companies using purposive sampling technique with the criteria of manufacturing companies listed on the Indonesian stock exchange that use the rupiah currency in their financial statements and publish annual reports that have been audited in full and have consistent data and pay dividends regularly. consistent throughout the study period. The results of the mediation comparison coefficient analysis show that the direct effect is 0.235727 while the indirect effect must be calculated by multiplying the indirect coefficient from structure 1, namely (-0.617330) x (0.136667) = - 0.0843. Because the direct relationship coefficient is greater than the indirect relationship coefficient, it can be said that the actual relationship is not able to mediate reinforced with a significance value above = 5%, which is 0.8125.